2006
DOI: 10.1073/pnas.0601107103
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory responses in a gustatory organ of the malaria vector mosquito Anopheles gambiae

Abstract: The proboscis is an important head appendage in insects that has primarily been thought to process gustatory information during food intake. Indeed, in Drosophila and other insects in which they have been identified, most gustatory receptors are expressed in proboscis neurons. Our previous characterization of the expression of AgOR7, a highly conserved odorant receptor (OR) of the Afrotropical malaria vector mosquito Anopheles gambiae in the labellum at the tip of the proboscis was suggestive of a potential ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
149
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(166 citation statements)
references
References 47 publications
6
149
2
Order By: Relevance
“…Here at least one sensillum that is reminiscent of the Cs. inornata T2 sensilla harbours at least two ORNs and responds to butylamine, aliphatic acids and several ketone compounds including acetophenone (Kwon et al 2006). The presence of this cryptic olfactory capacity in the primary gustatory organ of An.…”
Section: Aaor69 Agor69mentioning
confidence: 99%
See 4 more Smart Citations
“…Here at least one sensillum that is reminiscent of the Cs. inornata T2 sensilla harbours at least two ORNs and responds to butylamine, aliphatic acids and several ketone compounds including acetophenone (Kwon et al 2006). The presence of this cryptic olfactory capacity in the primary gustatory organ of An.…”
Section: Aaor69 Agor69mentioning
confidence: 99%
“…Recent electrophysiological studies, however, demonstrated that the labellum of An. gambiae is also sensitive to odorant stimuli including butylamine and several aliphatic carboxylic acids (Kwon et al 2006). Here at least one sensillum that is reminiscent of the Cs.…”
Section: Aaor69 Agor69mentioning
confidence: 99%
See 3 more Smart Citations